2002
DOI: 10.1021/ja017308q
|View full text |Cite
|
Sign up to set email alerts
|

Telomestatin, a Potent Telomerase Inhibitor That Interacts Quite Specifically with the Human Telomeric Intramolecular G-Quadruplex

Abstract: Telomestatin is a natural product isolated from Streptomyces anulatus 3533-SV4 and has been shown to be a very potent telomerase inhibitor. The structural similarity between telomestatin and a G-tetrad suggested to us that the telomerase inhibition might be due to its ability either to facilitate the formation of or trap out preformed G-quadruplex structures, and thereby sequester single-stranded d[T(2)AG(3)](n) primer molecules required for telomerase activity. Significantly, telomestatin appears to be a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
358
0
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(368 citation statements)
references
References 19 publications
2
358
0
8
Order By: Relevance
“…Telomerase activity was significantly inhibited by addition of 5 nM telomestatin ( Figure 1a). These results showed that telomestatin is a potent inhibitor of telomerase activity and were consistent with the previous report (Kim et al, 2002).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Telomerase activity was significantly inhibited by addition of 5 nM telomestatin ( Figure 1a). These results showed that telomestatin is a potent inhibitor of telomerase activity and were consistent with the previous report (Kim et al, 2002).…”
Section: Resultssupporting
confidence: 93%
“…In the BCR-ABL-positive leukemic cell lines OM9;22 and K562, telomestatin inhibits telomerase activity, resulting in telomere shortening and ultimately telomere dysfunction (Tauchi et al, 2003). Telomestatin interacts preferentially with intramolecular versus intermolecular G-quadruplex structures (Kim et al, 2002). Telomestatin is able to stabilize G-quadruplex structures that are formed from duplex human telomeric DNA as well as those formed from single-stranded DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptolepine stabilizes the F21MB quadruplex by 3 °C at 3 µM, whereas the best G4 ligands stabilize by 20 °C or more at 1 µM compound [44]. It is not a potent telomerase inhibitor (IC 50 = 9.4 µM); the best inhibitors described so far have an IC 50 of 50 nM or lower [37,44,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…A number of distinct chemical mechanisms have emerged for targeting DNA and RNA, but we will only consider the alkylating natural products here. The reader is referred to the reviews [51][52][53] for a comprehensive discussion of the different mechanisms such as non-covalent binders, 54 radical cleavage, 55 reactive oxygen species generation. 56 In the following section we will give an overview of different alkylation strategies that have evolved to target nucleic acids.…”
Section: Natural Products That Covalently Modify Nucleobasesmentioning
confidence: 99%